(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
Puberty is a developmental period that poses challenges for children with Autism Spectrum Disorder (ASD) due to limitations in understanding the physical, emotional, and social changes that occur in them. This study aims to describe the challenges faced by children with autism during puberty and the forms of adaptation and education needed to support their development. The study used a literature study method with a qualitative descriptive approach. Data were obtained from journal articles, books, and previous research results relevant to puberty in children with autism. Literature was selected based on topic suitability, then analyzed using content analysis techniques through the stages of identification, reduction, grouping themes, interpretation, and synthesis of findings. The results of the study indicate that children with autism experience pubertal changes similar to adolescents in general, but face greater difficulties in understanding bodily changes, maintaining personal hygiene, managing emotions, and understanding social boundaries and privacy. The research findings also indicate that appropriate sex education, the use of visual media, simple and consistent communication, and collaboration between parents and schools are effective strategies to help children with autism adapt during puberty. This study emphasizes the importance of structured support to support the independence and well-being of autistic children during adolescence.